What Explains Latin America's Low Share of Industrial Employment? - Sinha, Rishabh (World Bank, Washington, DC, 2019)
This paper investigates the relative importance of different channels in explaining the low share of industrial employment in Latin America relative to the economies that employ a large share of the workforce in industry. Differences in domestic final consumption shares play a pivotal role and can account for 50-70 percent of the industrial share gap. The paper finds limited support for the comparative advantage hypothesis, as differences in trading patterns account for less than 15 percent of the gap. More important are the differences in sectoral linkages and wage gaps which account for more than 30 percent of the industrial employment gap individually.